2020
DOI: 10.3389/fsurg.2020.598138
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Suprasellar Pituitary Adenoma Presenting With Temporal Lobe Seizures

Abstract: Seizures in patients with pituitary pathology are uncommon and typically secondary to electrolyte disturbances. Rarely, seizures have been described from mass effect related to large prolactinomas undergoing medical treatment. We describe a 54 year-old male who presented with a first-time generalized seizure, secondary to a pituitary macroadenoma compressing the left temporal lobe. His seizures abated after endoscopic endonasal debulking of the tumor. This report highlights isolated seizures as a potential sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Although many aspects of the molecular mechanisms of tumor invasion have been studied, the reasons for the aggressive growth of pituitary adenomas remain unclear [ 4 , 5 ]. The current study found that the main pathophysiology of invasive pituitary adenomas is a persistent state of cell proliferation and cell cycle disturbance [ 6 ]. Therefore, elucidating the molecular mechanism of invasive growth of invasive pituitary adenomas is particularly important for the prevention and treatment of invasive pituitary adenomas.…”
Section: Introductionmentioning
confidence: 99%
“…Although many aspects of the molecular mechanisms of tumor invasion have been studied, the reasons for the aggressive growth of pituitary adenomas remain unclear [ 4 , 5 ]. The current study found that the main pathophysiology of invasive pituitary adenomas is a persistent state of cell proliferation and cell cycle disturbance [ 6 ]. Therefore, elucidating the molecular mechanism of invasive growth of invasive pituitary adenomas is particularly important for the prevention and treatment of invasive pituitary adenomas.…”
Section: Introductionmentioning
confidence: 99%
“…While visual impairments and visual field defects (72%), followed by headache (13%), are the commonest preoperative presentations of these entities, seizures, particularly of the generalized tonic clonic type, are extremely rare and limited to a handful of case reports. 3,6,[8][9][10][11][12] (Table 2) Convulsions are hypothesized to occur when the tumour invades the suprasellar area and/or the nervous system, specifically the frontal and temporal lobes, generating an epileptogenic focus. 4 However, it is important to note that seizures are increasingly common in patients with prolactinomas, specifically those treated with dopamine agonists such as cabergoline and bromocriptine, as discussed in depth through multiple case studies and case series.…”
Section: Discussionmentioning
confidence: 99%
“…9,13,14 This is speculated to be due to the intratumoural hemorrhage that occurs during the medical treatment of prolactinomas, hence acting as an instigator for seizure development, as supported by MRI evidence of hemosiderin deposition in the medial temporal lobes of those patients. 6 Nevertheless, the index case of GTC seizures from a GCNFPA histologically diagnosed as a null cell adenoma is unique both in its clinical presentation and the surgical management employed in its resection. Presentations of seizures much less seizures as the only complaint in non-functioning PitNETs are observed in a very limited number of case reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations